PENERAPAN FUZZY AHP DAN TOPSIS UNTUK SELEKSI KANDIDAT PENERIMA BANTUAN RUMAH TIDAK LAYAK HUNI (RTLH) (STUDI KASUS : DESA BANTARWUNI) - Agus Tri Hidayat; Agus Priyanto; Andika Elok Amalia (Jurnal TAM (Technology Acceptance Model), 2017)
The selection process of recipient candidates of RTLH in Bantarwuni village didn’t computerize, so it takes a relatively long time and requires a lot of resources and become less effective. In this research, seletion process of recipient candidates of RTLH uses FAHP and TOPSIS method. Some of criterion to determine recipient candidates of RTLH are condition of the roof, condition of wall, condition of floor and air circulation. The calculation of the criteria weighting is done by using FAHP method. The result of the weighting criteria of the roof has a value of 0.5167, the weight of the criterion of the floor is 0.3350, the wall criterion weight is 0.1469 and the air circulation criterion is 0,0012 with the value of the consistency ratio (CR) of 0.039161. The ranking process is done by using TOPSIS method. Test results with 10 data samples have an accuracy of 100%.